Emerging Causes And Effects Of Inflation In Syria - Idlibi, Mona; Fadel, Hassan Mohamed (Latakia University Journal - Economic and Legal Sciences Series, 2020)
There are many reasons that led to the spread of the phenomenon of inflation in the case of political, economic and security instability, and new effects were not known in the case of natural inflation in the country, and Syria is still suffering from this instability of various forms in this research. Inflation rates during the years of the ongoing economic crisis and to identify at the most important new causes and the effects of inflation and the immediate solutions that can lead to mitigate the inflation possible and curb it as the talk about radical treatment requires a stable economic and political environment on the These distant monetary and fiscal policies are used and this is not currently available استجدت الكثير من الأسباب التي أدت إلى تفشي ظاهرة التضخم في حالة عدم الاستقرار السياسي والاقتصادي والأمني وظهرت أثار جديدة لم تكن معروفة في حالة التضخم الطبيعي في الدولة ، وسورية مازالت تعاني حتى هذه اللحظة من عدم الاستقرار بمختلف أشكاله حيث عمدت في هذا البحث تسليط الضوء على تصاعد معدلات التضخم خلال سنوات الأزمة الاقتصادية المستمرة والوقوف عند أهم الأسباب الجديدة والأثار الناجمة عن التضخم وما يمكن أن يتبعها من حلول فورية تؤدي للتخفيف ما أمكن من التضخم وتكبح جماحه باعتبار أن الحديث عن علاجه جذرياً يحتاج إلى بيئة اقتصادية وسياسية مستقرة على المدى البعيد تستخدم فيها سياسات نقدية ومالية وهذا غير متوفر حالياً.